ANALYSIS OF SOME FACTORS WHICH CONTRIBUTE TO NITRO INTOXICATION OF ANIMALS - Larisa CREMENEAC; Valentina ABRAMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The accumulation of nitro compounds in plants depends on several factors, in particular: the doses and frequency of incorporation of organic and mineral fertilizers in the soil, the amount of nitro compounds accumulated in soil and plants, climatic conditions, the period of plant physiological development, water insufficiency, etc. All of these factors contribute to the accumulation in quantities which exceed the admissible limit concentration (ALC) of nitro compounds in plants, including fodder. The main causes which contribute to the nitro intoxication of the animals are: the non-compliance of the rules on the storage and use of nitrogen fertilizers, the lack of zoo veterinary control over the quality of the fodder which contains amounts that exceed the ALC. The most sensitive to nitro intoxication are ruminants. The degree of nitrate hazard is mainly determined by the total toxicity of all metabolites formed in the fermentation process in the multi-chamber stomach of ruminant animals. Nitro intoxication of the animals occurs as a result of the penetration of nitro compounds into the body with food and drinking water which contain nitrites and nitrates that exceed ALC. The use of feed in animal ration, fodder and water with high nitrite and nitrate content leads to acute or chronic intoxication, which affects animal health and the quality of animal products.